Sex‐specific differences in T‐cell immune dysregulation and aberrant response to inflammatory stimuli in offspring exposed to maternal chronic inflammation. (28th December 2022) - Liu, Jin; Liu, Yang; Kirschen, Gregory; Liu, Anguo; Lei, Jun; Burd, Irina
Abstract: Problems: Maternal chronic inflammation (MI) can adversely affect offspring's immune development resulting in dysregulation of splenic T cells. Interleukin 1 beta (IL‐1β) contributes to mediating inflammation in the placenta to induce fetal toxicity and cause long‐term postnatal sequelae. In this study, we investigated how MI affects the T‐cell immune development from the fetal to the neonatal period and how offspring responded to postnatal IL‐1β challenge when exposed to an adverse intrauterine environment. We also extend these studies to examine the sex‐specific differences. Methods of Study: Time‐pregnant CD1 dams were administrated with four consecutive injections of mouse recombinant Interleukin‐1β (rIL‐1β) or phosphate‐buffered saline (PBS) from embryonic day (E)14 to E17. Pups were treated with rIL‐1β or PBS at postnatal day (PND)11 (pre‐weaning) or PND24 (post‐weaning). Pups' splenic immune cells were isolated and then characterized using flow cytometry. Results: At PND12, no differences were observed either in Ctrl or MI offspring. At PND25, we observed elevated amount of CD8 + T cells, descending CD4 + /CD8 + and Treg/Teff ratio in MI offspring. Pre‐weaning rIL‐1β administration did not affect T‐cell subpopulation in Ctrl pups while post‐weaning rIL‐1β administration increased T cells and CD8 + T cells and decreased CD4 + /CD8 + and Treg/Teff ratio in Ctrl offspring. Furthermore, pre‐weaning rIL‐1β administration decreased the frequency of T cells and Treg/Teff ratio in MI pups while post‐weaning rIL‐1β administration increased Tregs and Treg/Teff in MI pups. Regarding sex‐specific changes, we observed that at PND12, MI females exhibited higher CD4 + /CD8 + and Treg/Teff ratio than Ctrl females. At PND25, we observed elevated amount of CD8 + T cells, descending CD4 + /CD8 + and Treg/Teff ratio in MI Females, while MI males did not show any changes in T‐cell population. Pre‐weaning rIL‐1β administration decreased T‐cell frequency in both MI males and females and decreased Treg/Teff ratio only in MI females. Post‐weaning rIL‐1β administration increased Tregs and Treg/Teff ratio, and decreased CD4 + /CD8 + ratio in MI females. Conclusions: Prenatal‐inflammation‐exposed offspring exhibited dysfunctional T‐cell immunity and regulatory immune responses to postnatal challenges, showing both sex‐specific and age‐dependent differences. It could be speculated from our results that experiencing environmental challenges or adverse stimuli during the vulnerable intrauterine period, such as maternal chronic inflammation, stress, preterm birth, and chronic infections, might induce fetal immune reprogramming and potentially cause long‐term adverse immune consequences, such as a predisposition to allergic diseases, autoimmune diseases, asthma and pediatric mortality of unknown etiology.